Chemical oxidation applications for industrial wastewaters. - Tünay, Olcay, ....-; Arslan-Alaton, Idil, ....-; Kabdasli, Isik, ....- (London : IWA, 2010)
This book covers the most recent scientific and technological developments (state-of-the-art) in the field of chemical oxidation processes applicable for the efficient treatment of biologically-difficult-to-degrade, toxic and/or recalcitrant effluents originating from different manufacturing processes. It is a comprehensive review of process and pollution profiles as well as conventional, advanced and emerging treatment processes & technologies developed for the most relevant and pollution (wet processing)-intensive industrial sectors.It addresses chemical/photochemical oxidative treatment processes, case-specific treatability problems of major industrial sectors, emerging (novel) as well as pilot/full-scale applications, process integration, treatment system design & sizing criteria (figure-of-merits), cost evaluation and success stories in the application of chemical oxidative treatment processes.Chemical Oxidation Applications for Industrial Wastewaters is an essential reference for lecturers, researchers, industrial and environmental engineers and practitioners working in the field of environmental science and engineering.